SURGICAL TREATMENT OF DISTROPHICAL BONE KISTS BY TITANIUM NIKELID POROUS MATERIALS IN CHILDREN - G. V. Slizovskiy; L. A. Sitko; I. I. Kuzhelivskiy (Бюллетень сибирской медицины, 2015)
The article presents the results of bone kists treatment by porous granular titanium nikelid materials. A comparative examination with standard treatment technology group demonstrated high efficiency of a proposed method. Porous granular titanium nikelid materials possess mechanical strength, optimization of regeneration  at the expense of osteoinductivity and  allow you  to  effectively fill the cavity with a complex anatomical structure.